2021
DOI: 10.1111/psyg.12764
|View full text |Cite
|
Sign up to set email alerts
|

Depressed mood and frailty among older people in Tokyo during the COVID‐19 pandemic

Abstract: Background The study aim was to identify depressed mood and frailty and its related factors in older people during the coronavirus disease 19 pandemic. Methods Since 2010, we have conducted questionnaire surveys on all older residents, who are not certified in the long‐term care insurance, living in one district of Tokyo municipality. These residents are divided into two groups by birth month, that is those born between April and September and those born between October and March, and each group completes the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 30 publications
(32 reference statements)
1
19
1
Order By: Relevance
“… 26 , 27 Among older residents in a district of Tokyo, Okamura et al reported that between 2018 and April 2020, when the first state of emergency was declared, the proportion of people with depressed mood increased from 29% to 38%, and the proportion of people with frailty increased from 10% to 16%. 28 In our study, the prevalence of depressed mood was 20.8% in the Continued group and 37.4% in the Discontinued group, while it was 24.2% and 35.4% for oral frailty. It was noteworthy that the study participants lived in a city in which the COVID‐19 pandemic was not as serious as in metropolitan areas, with only 29.0 cumulative cases per 100,000 population as of January 2021.…”
Section: Discussionmentioning
confidence: 40%
See 1 more Smart Citation
“… 26 , 27 Among older residents in a district of Tokyo, Okamura et al reported that between 2018 and April 2020, when the first state of emergency was declared, the proportion of people with depressed mood increased from 29% to 38%, and the proportion of people with frailty increased from 10% to 16%. 28 In our study, the prevalence of depressed mood was 20.8% in the Continued group and 37.4% in the Discontinued group, while it was 24.2% and 35.4% for oral frailty. It was noteworthy that the study participants lived in a city in which the COVID‐19 pandemic was not as serious as in metropolitan areas, with only 29.0 cumulative cases per 100,000 population as of January 2021.…”
Section: Discussionmentioning
confidence: 40%
“…Social participation is reported to have a preventive effect on the onset of depression 26,27 . Among older residents in a district of Tokyo, Okamura et al reported that between 2018 and April 2020, when the first state of emergency was declared, the proportion of people with depressed mood increased from 29% to 38%, and the proportion of people with frailty increased from 10% to 16% 28 . In our study, the prevalence of depressed mood was 20.8% in the Continued group and 37.4% in the Discontinued group, while it was 24.2% and 35.4% for oral frailty.…”
Section: Discussionmentioning
confidence: 99%
“…23 is regarded as a factor of new incidence of frailty and prevalence of depressed mood has been shown to have increased during the COVID-19 pandemic. 13,30 Thus, it is inferred that this item affects frailty regardless of the occurrence of the pandemic. In contrast, the response of "No" for No.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, there are 36 studies [4,5,8–41] with 58,028 people included in this systematic-review. Data extraction included the baseline characteristics of aging adults, their lifestyle habits, their accompanying diseases, and whether they had experienced falls.…”
Section: Methodsmentioning
confidence: 99%
“…Several recent studies have identified severity of frailty across various conditions, including old age, female sex, and reduced concentration and motivation. [4,5,8–41] However, high-quality systematic reviews are still in demand. Overall, we conducted this project to study the risk factors for frailty.…”
Section: Introductionmentioning
confidence: 99%